Effectiveness Of Rice Husk Charcoal to Improve Breakdown Voltage of Used Transformer Oil - Amelya Indah Pratiwi; Muhammad - Asri (Jurnal Teknologi Terpadu, 2022)
Environmental pollution due to the burning of rice husk biomass and discarded transformer oil has a negative impact on the environment and livings. Utilization of rice husk biomass apart from being used as animal feed, fertilizer, can also be used as a purification of used transformer oil so that used transformers that were originally going to become waste can be reused in a long period of time. This study aims to analyze the effectiveness of rice husk activated charcoal in improving the breakdown voltage of used nynas libra transformer oil. The activator material used in rice husk charcoal is NAOH 30% as much as 100 ml with a chemical method for the activation process. To obtain the effectiveness value in terms of the percentage increase in breakdown voltage before and after purification, then the value of the voltage of the two test treatments is also reviewed against the standard breakdown voltage of transformer oil SPLN 49-1. The results showed that the average breakdown voltage increase of 5 times in each process was 166.99%. It can be concluded that the use of rice husk activated charcoal as a purification agent is effective in improving the breakdown voltage of used transformer oil